KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI KELAS X DI SMA NEGERI 1 PAYAKUMBUH - Hidayatullah, Riska; Arief, Ermawati; Noveria, Ena (Universitas Negeri Padang, 2018)
ABSTRACTThe article was written to describe the reading comprehension skills of exposition text with the skills of writing exposition students class X SMAN 1 Payakumbuh. The type of this stuudy is quantitative research by using descriptive method. The research design used is correlational. Population in this study is students of grade X SMAN 1 Payakumbuh registered in the academic year 2017/2018 amounted to 396 students. Sample were taken using proportional random sampling. Based on the result of this study, it can be concluded that correlation between reading skill with writing skill of exposition text student class X SMAN 1 Payakumbuh with convidence 95% with degree of freedom n-1; t-count> t-table (8,37)> (1.67 ). Therefore, reading comprehension skills of expository text has a correlation the skills of writing exposition textÂ Kata kunci: korelasi, membaca pemahaman, menulis, teks eksposisi